PERAN SATUAN PENGAWASAN INTERN DAN PENERAPAN PENGENDALIAN INTERNAL TERHADAP PENCAPAIAN GOOD UNIVERSITY GOVERNANCE PADA PERGURUAN TINGGI DI KOTA BENGKULU - Dri Asmawanti S; Siti Aisyah (UNIB Press, 2017)
The research was aimed to examine and obtain empirical evidence of the influence from role of internal control unit and controling system internal to achievement of Good University Governance in College with state in Bengkulu City. The data was collect from questioner that direclty spread to the all responden. The result of this study explained that role of internal control units and controlling system internal has positively significance influence to achievement of Good University Governance.Keywords : Internal control unit, controlling system internal